Percutaneous endoscopic gastrostomy in children - Jye Hae Park; SeonKyeong Rhie; Su Jin Jeong (Korean Pediatric Society, 2011)
PurposePercutaneous endoscopic gastrostomy (PEG) can improve nutritional status and reduce the amount of time needed to feed neurologically impaired children. We evaluated the characteristics, complications, and outcomes of neurologically impaired children treated with PEG.MethodsWe retrospectively reviewed the records of 32 neurologically impaired children who underwent PEG between March 2002 and August 2008 at our medical center. Forty-two PEG procedures comprising 32 PEG insertions and 10 PEG exchanges, were performed. The mean follow-up time was 12.2 (6.6) months.ResultsMean patient age was 9.4 (4.5) years. The main indications for PEG insertion were swallowing difficulty with GI bleeding due to nasogastric tube placement and/or the presence of gastroesophageal reflux disease (GERD). The overall rate of complications was 47%, with early complications evident in 25% of patients and late complications in 22%. The late complications included one gastro-colic fistula, two cases of aggravated GERD, and four instances of wound infection. Among the 15 patients with histological evidence of GERD before PEG, 13 (87%) had less severe GERD, experienced no new aspiration events, and showed increased body weight after PEG treatment.ConclusionPEG is a safe, effective, and relatively simple technique affording long-term enteral nutritional support in neurologically impaired children. Following PEG treatment, the body weight of most patients increased and the levels of vomiting, GI bleeding, and aspiration fell. We suggest that PEG with post-procedural observation be considered for enteral nutritional support of neurologically impaired children.